A abordagem de martingais para o estudo de ocorrência de palavras em ensaios independentes - Masitéli, Vanessa (2017)
Let Xn be a sequence of i.i.d. random variables taking values in an enumerable alphabet. Given a finite collection of words, we observe this sequence till the moment T at which one of these words appears as a run. In this work we apply the martingale approach introduced by Li (1980) and Gerber e Li (1981) in order to study the waiting time until one of the words occurs for the first time, the mean of T and the probability of a word to be the first one to appear.